Monosynaptic responses of ventral roots of spinal cord in experimental diabetes mellitus - Rodinsky A.G.; Zinov’yeva E.G.; Romanenko L.A. (Medičnì Perspektivi)
In intact rats and rats with experimental diabetes mellitus (DM) threshold, chronaxia, latent period, duration and amplitude of monosynaptic discharges of ventral root, as well as refractory periods in response to its paired stimulation were analyzed. There as found out increase in the threshold of excitability by 2 times (p<0,01), increases in the total duration of action potential by 25% (p<0,001), and latent period by 32% (p<0,05) and decrease in its amplitude by 11% (p>0,05). In the response to paired stimulation there was obtained a significant increase in the amplitude of action potential under experimental DM in the interval of 2-5 ms between stimulation. There was made a conclusion that in DM a decrease in excitability and conductivity of the spinal cord structures at the level of L5, occurred and a tendency to increase of ability to summation of excitation was seen.